Empirical research on K-16 climate education: A systematic review of the literature. Issue 3 (26th July 2021) - Bhattacharya, Devarati; Carroll Steward, Kimberly; Forbes, Cory T.
Abstract: Developing understanding about the Earth's climate and the phenomenon of global climate change (GCC) is essential for all students, our future citizens and decision-makers. Recent implementation of the Next Generation Science Standards (NGSS) has intensified the focus on teaching and learning of the Earth's climate and GCC in formal learning environments. Concurrently, the empirical research associated with climate education has also increased. We used an exhaustive, stepwise process to search for and identify relevant literature, systematically analyzing 178 empirical, peer-reviewed studies focused on climate literacy and education in formal K-16 settings. Thematic analysis was then used to identify focal research areas, and describe 1) trends in education research focused on the Earth's climate and GCC, 2) student knowledge, conceptions, beliefs, and their learning about the Earth's climate and GCC, and 3) teacher knowledge, conceptions, beliefs, practices, and their preparation about teaching Earth's climate and GCC. The results of this review summarize challenges faced by both teachers and students in developing their knowledge about GCC. Findings from this literature review will help guide design of curriculum and instruction for climate change content in K-16 classrooms, as well as professional development and teacher preparation about Earth's climate and GCC in K-16 contexts.